Probability Model Based Coverage-Enhancing Algorithm for WSNs of Nodes' Adjustable Movement Pattern - Junjie Huang; Haiping Huang; Peng Sun; Ruchuan Wang; Xun Wei (International Journal of Distributed Sensor Networks)
Aimed at the defects of current coverage-enhancing algorithms, firstly the probability model is introduced into the coverage-enhancing algorithm of the directional sensor network based on the virtual potential field, and the probability model would have an impact on the location of the centroid. Secondly, to the boundary coverage, through the simulation of typical algorithms which consider the boundary repulsion, it finds that the coverage rates of the corners are much lower than the overall coverage. To add a vertex force on the corner is essential and to some extent would reduce the gap between them. Finally, based on the random deployment of sensor nodes, a novel algorithm is proposed which determines whether the sensor node rotates or moves along fixed direction according to the coverage effect, named as PRMCA (probability model based rotate or move along fixed direction coverage-enhancing algorithm). A set of simulation experiments verify the performance of the proposed algorithm.